Improving Antioxidant Capacity in Children With Autism: A Randomized, Double-Blind Controlled Study With Cysteine-Rich Whey Protein - Castejon, Ana Maria; Spaw, Jordan Ashley; Rozenfeld, Irina; Sheinberg, Nurit; Kabot, Susan; Shaw, Alexander; Hardigan, Patrick; Faillace, Rogerio; Packer, Edward E. (Frontiers in Psychiatry, 2021)
Previous studies indicate that children with autism spectrum disorder (ASD) have lower levels of glutathione. Nutritional interventions aim to increase glutathione levels suggest a positive effect on ASD behaviors, but findings are mixed or non-significant. A commercially available nutritional supplement comprising a cysteine-rich whey protein isolate (CRWP), a potent precursor of glutathione, was previously found to be safe and effective at raising glutathione in several conditions associated with low antioxidant capacity. Therefore, we investigated the effectiveness of a 90-day CRWP intervention in children with ASD and examined whether intracellular glutathione improvements correlated with behavioral changes. We enrolled 46 (of 81 screened) 3 to5-year-old preschool children with confirmed ASD. Using a double-blind, randomized, placebo-controlled design, we evaluated the effectiveness of daily CRWP (powder form: 0.5 g/kg for children <20 kg or a 10-g dose for those >20 kg), compared with placebo (rice protein mimicking the protein load in the intervention group), on glutathione levels and ASD behaviors assessed using different behavioral scales such as Childhood Autism Rated Scale, Preschool Language Scale, Social Communication Questionnaire, Mullen Scales of Early learning, Childhood Behavioral Checklist and the parent-rated Vineland Adaptive Behavior Scale, 2nd edition (VABS-II). Forty children (CRWP, 21; placebo, 19) completed the 90-day treatment period. Improvements observed in some behavioral scales were comparable. However, the VABS-II behavioral assessment, demonstrated significant changes only in children receiving CRWP compared to those observed in the placebo group in the composite score (effect size 0.98; 95% confidence intervals 1.42 to 4.02; p=0.03). Further, several VABS-II domain scores such as adaptive behavior (p=0.03), socialization (p=0.03), maladaptive behavior (p=0.04) and internalizing behavior (p=0.02) also indicated significant changes. Children assigned to the CRWP group showed significant increases in glutathione levels (p=0.04) compared to those in the placebo group. A subanalysis of the VABS-II scale results comparing responders and non-responders in the CRWP group identified older age and higher levels of total and reduced glutathione as factors associated with a response. CRWP nutritional intervention in children with ASD significantly improved both glutathione levels and some behaviors associated with ASD. Further studies are needed to confirm these results.